(untitled) (International Journal of Management and Sustainability, 2015)
The paper deals with complete analysis of the liability of insurer in the international carriage of goods. The paper lays down the international instruments that govern the field and the extent to which they affect the liability of the insurer. The paper also analyzes the conflict of laws issues related to the international insurance. The paper further does a study of the concepts related to the international insurance of carriage of goods and liability of the insurer. The focus has been on the common law principles. AIM AND OBJECTIVE: The paper analyzes the extent of liability of the insurance company. SCOPE: Due to the paucity of time and space the researchers have limited the scope of the paper to the liability of insurance company in general sense. There is also a lacuna in International Law on this particular aspect of insurer’s liability thus more attention is paid to common law principles and the Marine Insurance Act, 1906. The author has referred to case laws from different jurisdictions to give a wider prospective but has not done a comparative study of different legal regimes. RESEARCH QUESTION: What is the importance of International Insurance? What are the instruments governing the International Insurance? What is the extent of liability of the insurer? PROBLEM STATEMENT: The existing legal setup is not in itself equipped to deal with the issue like liability of the insurer in international insurance and thus codification is required. RESEARCH METHODOLOGY: A descriptive style of writing has been used throughout the paper. Doctrinal method of research has been adopted.